Leveling Up Mathematical Skills: The Effectiveness of Game-Based Learning - Cayang, Juzzel Amor; Ursabia, Eziel Mae (Journal of Interdisciplinary Perspectives, 2024)
This quantitative study, using an experimental approach, aimed to determine the effectiveness of game-based learning in teaching mathematics. The respondents were fourth-grade pupils in an elementary school in Aleosan, North Cotabato, Philippines. Data were gathered using a pre-test questionnaire adopted by the researcher and a researcher-made post-test questionnaire validated by experts. The data were analyzed using weighted means and paired and unpaired t-tests. Results revealed that academic performance in mathematics during the pre-test was poor. However, there was a highly significant difference between the scores before and after the intervention. There was also a significant difference between the control and experimental groups (t=-2.337, p=0.022), with the experimental group (M=19.18) scoring significantly higher than the control group (M=16.31). Based on the findings, it can be affirmed that implementing game-based learning strategies in mathematics instruction is highly effective, resulting in a notable enhancement of learners' academic performance compared to conventional teaching methods. Moreover, the results encourage teachers to revisit their instructional materials and integrate game-based learning materials aligned with specific learning objectives. Additionally, the study provides substantial evidence that game-based learning significantly enhances academic performance in mathematics compared to traditional instructional resources.